Perspektif Sekala-Niskala Penghidupan Masyarakat Bali Terdampak Covid-19 - Slamet Subekti (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2021)
This paper is based on a descriptive study of the phenomenon of the COVID-19 pandemic and the socio-economic and cultural conditions of the Balinese people. The data used are sourced from published data from the media. Data were collected through non-participant observation, then processed descriptively. The discussion here is presented in four parts, the first is the condition of the Balinese people affected by the COVID-19 pandemic. Second, mapping the livelihoods of the Balinese people. Third, the response to the COVID-19 pandemic in Sekala and Niskala perspectives, and fourth is a conclusion. This discussion has concluded as follows: The livelihoods of the Balinese people in general have been seriously affected by the COVID-19 pandemic. This pandemic resulted in a drastic decrease in the number of tourist visits to Bali, so that the tourism sector and its supporting infrastructure has collapsed. In turn, the income of informal sector workers decreased, also faced by business owners. Based on the philosophy of Hinduism, Balinese people responded to the pandemic phenomenon, both physically (Sekala) which presupposes concrete rational actions by adhering to health protocols, and metaphysical (Niskala) which presupposes the performed of cosmic purification rituals. The future of the Balinese people's livelihood after the pandemic is expected to continue through the restoration of the cultural tourism sector by maintain environmental sustainability and developing the potential for featured agricultural cultivation, including the Bali coffee commodity